Donor parental determination for breeding the RD41 rice cultivar to improve bacterial blight resistance - Sontornkarun, Torsakoon; Chankaew, Sompong; Sanitchon, Jirawat (วารสารแก่นเกษตร, 2020)
Bacterial blight (BB) caused by Xanthomonas oryzae pv. Oryzae (Xoo) is one of the most critical rice diseases in Southeast Asia. RD41 is one of the most popular rice varieties in Thailand’s irrigation areas due to its early maturity and high productivity. However, it is highly susceptible to BB. To improve RD41’s BB resistance, an experimental breeding program was conducted, in which ten rice varieties, five Thai recommended, three newly introduced varieties and two susceptible check were evaluated in order to identify a parental variety. Three Xoo isolates collected from Thailand’s Northeast region were selected for artificial inoculation. Lesion length was observed at five days after inoculation (DAI). IR62266, one of the newly introduced varieties, was resistant to all Xoo isolates, and was greatest in broad-spectrum resistance (BSR); whereas the Thai varieties SPR1, SPR60, and SPR90 were susceptible with 0.00 BSR. KDML105, the susceptibility check variety demonstrated a high percentage severity (85%), whereas IR62266 was 35.5% at 9 DAI. Likewise, the areas under the disease development progress curve (AUDPC) was low for most of the proposed varieties. To confirm resistance, the F2 population from a cross of RD41 X IR62266 illustrated a ratio of single dominant resistance. IR62266 has proven to have a high potential as a donor parent for breeding programs in which to achieve successful BB resistance.